Barbie. Dolphin magic [videorecording (DVD)] (Universal Pictures Home Entertainment, 2018)
Join Barbie and her sisters Skipper, Stacie and Chelsea as they go on an adventure to a tropical island where Ken is doing a marine biology internship. After finding a family of gemstone dolphins being held captive by Marlo, the person Ken is interning with, they must join forces with a mysterious friend named Isla to save them before Marlo sends them away.